Students’ and Librarians’ Attitude Towards Book Theft, Mutilation and Misplacement in Engineering College Libraries - Parvathamma, N.; Anandhalli, Gavisiddappa (Journal of Information and Knowledge, 2001)
In the last few years, librarians of the academic institutions are more worried by their patrons’ delinquent acts which have begun to threaten the resources and services of their libraries. Of the 1254 students sampled from eight engineering colleges in Karnataka State, India, 515 (41 %) admitted to stealing books, 536 students (42.7%) admitted to mutilating books, while 564 students (45%) admitted to have intentionally misplaced books at least once in their libraries, Non-delinquent students amounted to 690 (55%) of the sample. When students come acros’s books being stolen/mutilated/misplaced by their friends they would either ask them to stop such act report to librarian, or just ignore it. The study revealed that high cost of books lack of photocopying facility and library environment are the major reasons for such delinquent acts of the students. Warning the delinquent students against such acts, withdrawal of their library membership, or imposing penalty are the punishment suggested by students and librarians. Preventive measures suggested include provision of more copies of text books. provision of photocopying facility at affordable cost, and organizing regular library tour and orientation talks in the library. A positive association is observed in the attitude of students and librarians in the above areas, even though the extent of association varies.